2020
DOI: 10.1007/s13555-020-00442-3
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis is Associated with a High Comedication Burden: A Population Based Register Study

Abstract: Introduction: A large body of evidence supports the association between psoriasis and concomitant diseases. However, the study of comedication for these diseases in patients with psoriasis is limited. The current study aimed to investigate the prescription and drug dispensation for comorbidity associated with psoriasis. Methods: We conducted a retrospective casecontrol study from 9 April 2008 until 1 January 2016 using an electronic medical records database covering the entire population of the County of Jönkö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
(55 reference statements)
0
14
0
2
Order By: Relevance
“…Disease severity was assessed according to selfreported body surface area (BSA) and psoriasis was categorized as mild (BSA \ 3), moderate (BSA between 3 and 10), or severe (BSA $ 10). Impact on quality of life was determined according to the Dermatology Life Quality Index (DLQI) and effect on quality of life was categorized as no (DLQI of 0-1), small (DLQI of 2-5), moderate (DLQI of 6-10), very large (DLQI of [11][12][13][14][15][16][17][18][19][20], and extremely large (DLQI of 21-30). 22 EuroQoL 5 Dimensions 5 Levels (EQ-5D-5L) were used to measure general health.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease severity was assessed according to selfreported body surface area (BSA) and psoriasis was categorized as mild (BSA \ 3), moderate (BSA between 3 and 10), or severe (BSA $ 10). Impact on quality of life was determined according to the Dermatology Life Quality Index (DLQI) and effect on quality of life was categorized as no (DLQI of 0-1), small (DLQI of 2-5), moderate (DLQI of 6-10), very large (DLQI of [11][12][13][14][15][16][17][18][19][20], and extremely large (DLQI of 21-30). 22 EuroQoL 5 Dimensions 5 Levels (EQ-5D-5L) were used to measure general health.…”
Section: Methodsmentioning
confidence: 99%
“…32 Along these lines, we found an increased use of nonsteroidal antiinflammatory drugs, opioids, paracetamol, and gabapentin with increased severity of skin symptoms, which could support the notion of analgesic use as a way of alleviating symptom in patients with psoriasis. 18 When adjusting for joint pain, the apparent association between skin pain or itch and use of analgesics was no longer observed. Additionally, use of analgesics was highly associated with joint pain, which more likely indicated the higher use of analgesics among patients with psoriasis to be a treatment of joint pain rather than skin symptoms.…”
Section: Atcmentioning
confidence: 98%
See 1 more Smart Citation
“…Another factor which further complicates the management of psoriasis that many patients are on polypharmacy because of their comorbidities. Duvetorp et al, 39 in a population-based register study, reported that polypharmacy was very common in patients with psoriasis, with only 1.3% of all patients being without any prescription. Thus, the management of patients with psoriasis becomes complicated because of the increased risk of drug–drug interactions.…”
Section: Use Of Apremilast For Plaque Psoriasis In Special Populationsmentioning
confidence: 99%
“…Another 2317 studies were removed after screening for titles and abstracts, and the remaining 159 were subject to full-text reviews, from which 146 were excluded for the following reasons: case report and case series (n = 49); not original research articles (n = 41); not English (n = 6); inappropriate data (n = 38); not being confirmed if drugs were taken before psoriasis diagnosis (n = 2); inappropriate study design (n = 2); and repeated study population (n = 8). Finally, 13 studies [11][12][13]15,16,[24][25][26][27][28][29][30][31] with 6 378 116 individuals were included for meta-analysis, the characteristics of which are presented in Table 1. Of these, 5 were cohort studies, 16,[25][26][27]29 and 8 were casecontrol studies.…”
Section: Identification and Characteristics Of The Included Studiesmentioning
confidence: 99%